PENGARUH MOTIVASI, KOMITMEN ORGANISASI DAN FASILITAS MENGAJAR TERHADAP KEPUASAN KERJA GURU DI SEKOLAH MENENGAH PERTAMA ( SMP ) NEGERI 1 PANGKALAN SUSU KABUPATEN LANGKAT - Poppy Sri Istiqlalia Dewanti Nuswantari (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The formulation of the problem in this study are: Does motivation, organizational commitment and teaching facilities partially and simultaneously affect the job satisfaction of teachers in SMP Negeri 1 Pangkalan Susu Kabupaten Langkat. This study aims to determine the effect of motivation, organizational commitment and teaching facilities on teacher job satisfaction in SMP Negeri 1 Pangkalan Susu Kabupaten Langkat. With the sampling technique in total sampling, the sample in this study was the entire population of 38 teachers in SMP Negeri 1 Pangkalan Susu Kabupaten Langkat, because the principal of SMP Negeri 1 Pangkalan Susu Kabupaten Langkat and researchers were not sampled. The results of this study indicate; motivation has a positive and significant effect on teacher satisfaction; organizational commitment has a positive and significant effect on teacher satisfaction; facilities a positive and significant effect on teacher satisfaction; motivation, organizational commitment and facilities have a positive and significant effect on teacher satisfaction.